Evaluation of Artificial Sweeteners, Microbiological Contamination, and Hygiene and Sanitation of Tea Beverages - Rachma Anggaratih; Ratna Yulistiani; Rahmawati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The high incidence of diarrhea in Rungkut District, Surabaya, which reached 3,341 cases, highlights critical concerns regarding the safety of beverages sold at container-based outlets. This study aimed to evaluate the food safety of iced tea beverages sold by container-based vendors in Rungkut District by analyzing the presence of artificial sweeteners (saccharin and cyclamate), assessing microbiological contamination (TPC, Coliform bacteria, and Escherichia coli), and examining their relationship with vendors' hygiene and sanitation practices. A descriptive survey with a cross-sectional approach was conducted, involving interviews, observation, and laboratory analysis for 20 container-based tea vendors selected through purposive sampling. Data were statistically analyzed using Fisher's exact tests at a 95% confidence level (p<0,05). Laboratory results showed that 100% of the tea samples were negative for saccharin and cyclamate. However, microbiological evaluation revealed that 85% of the samples failed to meet the national safety standard (PerBPOM No. 13 Year 2019) with critically high TPC values ranging from 47×103 to 134×105 CFU/mL. Furthermore, 80% of the samples exceeded the Coliform safety limit (<1.8 MPN/mL), although 100% of the samples were negative for Escherichia coli. Statistical analysis confirmed there was no significant relationship (p>0.05) between hygiene sanitation factors (personal hygiene, equipment sanitation, serving sanitation, and environmental sanitation) and the microbiological contamination levels, suggesting external risk factors such as raw water or contaminated ice blocks as the primary sources of contamination. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 6: Clean Water and SanitationSDG 12: Food Safety